2006
DOI: 10.1165/rcmb.2005-0376oc
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Confers Antiinflammatory Effects in Murine Macrophages via the MKK3/p38 MAPK Pathway

Abstract: Caveolin-1 has been reported to regulate apoptosis, lipid metabolism, and endocytosis in macrophages. In the present study, we demonstrate that caveolin-1 can act as a potent immunomodulatory molecule. We first observed caveolin-1 expression in murine alveolar macrophages by Western blotting and immunofluorescence microscopy. Loss-of-function experiments using small interfering RNA showed that down regulating caveolin-1 expression in murine alveolar and peritoneal macrophages increased LPS-induced proinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
155
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(172 citation statements)
references
References 50 publications
13
155
4
Order By: Relevance
“…Most of the transcription factor binding sites are also present in the human and bovine genes, suggesting that the regulation of caveolin-1 expression is conserved among mammals. These observations are supported by previous reports showing that activation of protein kinase A downregulates caveolin-1 protein expression (66) and that cytokine production by caveolin-1 also involves the MAPK kinase 3/p38 MAPK pathway (67).…”
Section: Discussionsupporting
confidence: 90%
“…Most of the transcription factor binding sites are also present in the human and bovine genes, suggesting that the regulation of caveolin-1 expression is conserved among mammals. These observations are supported by previous reports showing that activation of protein kinase A downregulates caveolin-1 protein expression (66) and that cytokine production by caveolin-1 also involves the MAPK kinase 3/p38 MAPK pathway (67).…”
Section: Discussionsupporting
confidence: 90%
“…Other potentially important sequelae of cav-1 deletion may include altered regulation of apoptosis and inflammation as suggested by other recent studies (20,22). These additional functions of cav-1 may be relevant since pulmonary hypertension is associated with endothelial cell-specific apoptosis and considerable vascular inflammation.…”
mentioning
confidence: 78%
“…For example, caveolin-1 deficient macrophages display impaired phagocytosis [19]. Wang et al [20] demonstrated that caveolin-1 acts as a potent immunomodulatory effecter molecule in murine alveolar and peritoneal macrophages. They showed that caveolin-1 has a protective role for inflammation by suppression of pro-inflammatory cytokine production (TNF-a and IL-6) and augmentation of anti-inflammatory cytokine production (IL-10) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [20] demonstrated that caveolin-1 acts as a potent immunomodulatory effecter molecule in murine alveolar and peritoneal macrophages. They showed that caveolin-1 has a protective role for inflammation by suppression of pro-inflammatory cytokine production (TNF-a and IL-6) and augmentation of anti-inflammatory cytokine production (IL-10) [20]. Thus, it is tempting to speculate that caveolin-1 in activated microglia participates in modulation of inflammation in the brain in response to excitotoxic insults.…”
Section: Discussionmentioning
confidence: 99%